Pemanfaatan Energi Biogas untuk Pembangkit Listrik di Desa Tuwang Kecamatan Karanganyar Kabupaten Demak - Muhammad Sukron; Iskendar Iskendar (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2020)
The Increase of energy demand in Indonesia causes the need for alternative energy to replace fossil energy. One of alternative energy is renewable energy that obtained from nature freely. Tuwang Village in Karanganyar District, Demak Regency has the potential for renewable energy from methane gas produced by cow dung on farms. Cow dung is tested in the laboratory to take the methane gas content. Two chambers biodigester from fiberglass are used to ferment and hold biogas which is then used as fuel on the stove. From 171 kg of cow manure that mixed with water in a ratio of 1:3, the ideal digestification time with the highest energy production of 689 kJ is 22 days. The average of CH4 composition is around 50% from the total of biogas content. The total energy obtained during the water heating process is 4.32 MJ, smaller than the theoretical energy calculation (20,52 MJ). Based on the results of experiments, it can be estimated that biogas energy generated from Tuwang Village each day is 40,42 MJ. Biogas energy power plant can use a genset or stirling engine with 468 Watt of power. This power can be used for neighborhood association lighting needs.